Geographical Perspective on the Development of Halal Tourism in Sabang City - Sugiharto, Sugiharto; Rahmadi, M Taufik; Pratama, Alvin; Yuniastuti, Eni; Pratiwi Sembiring, Yolanda; Fazera, Della; Arbiansyah, Arbiansyah (Tunas Geografi, 2025)
Indonesia is one of the countries with the largest Muslim population in the world that has great potential to develop halal tourism. The purpose of this study is to analyze the development of halal tourism in Sabang City based on the potential, cultural and religious influence in Sabang City, the suitability and availability of tourist facilities in meeting the needs of Muslim tourists, as well as the promotion and marketing system of halal tourism in Sabang City in the domestic and international markets. The research method used in this study is qualitative research using descriptive analysis. The results of the study show that Sabang City has the potential for natural, nautical, religious, heritage, culinary, tourist villages, and artificial tourism for the development of halal tourism that respects Islamic values. Aceh's culture, which is thick with Islamic religious values, affects the development of halal tourism in Sabang City by ensuring that all aspects of tourism are in accordance with Islamic law including dress rules on the beach, halal food, and the availability of places of worship in tourist destinations. The existence of facilities that suit the needs of Muslim tourists, such as tourist attractions, halal-certified inns and restaurants, Islamic banking services, worship facilities and transportation facilities that comply with sharia principles further strengthens the attractiveness of Sabang City as a halal tourist destination. Promotional activities carried out by tour managers increase the acceptance, purchase, and loyalty of tourism products through international promotions such as Sail Sabang and Sabang Marine Festival, as well as domestic promotions with government support, social media marketing, and cooperation with travel.